On the interplay between downwelling, deep convection and mesoscale eddies in the Labrador Sea - Georgiou, Sotiria; van der Boog, Carine G.; Brüggemann, Nils; Ypma, Stefanie L.; Pietrzak, Julie D.; Katsman, Caroline A. (Ocean Modelling, 2019)
In this study, an idealized eddy-resolving model is employed to examine the interplay between the downwelling, ocean convection and mesoscale eddies in the Labrador Sea and the spreading of dense water masses. The model output demonstrates a good agreement with observations with regard to the eddy field and convection characteristics. It also displays a basin mean net downwelling of 3.0 Sv. Our analysis confirms that the downwelling occurs near the west Greenland coast and that the eddies spawned from the boundary current play a major role in controlling the dynamics of the downwelling. The magnitude of the downwelling is positively correlated to the magnitude of the applied surface heat loss. However, we argue that this connection is indirect: the heat fluxes affect the convection properties as well as the eddy field, while the latter governs the Eulerian downwelling. With a passive tracer analysis we show that dense water is transported from the interior towards the boundary, predominantly towards the Labrador coast in shallow layers and towards the Greenland coast in deeper layers. The latter transport is steered by the presence of the eddy field. The outcome that the characteristics of the downwelling in a marginal sea like the Labrador Sea depend crucially on the properties of the eddy field emphasizes that it is essential to resolve the eddies to properly represent the downwelling and overturning in the North Atlantic Ocean, and its response to changing environmental conditions.